2021
DOI: 10.15537/smj.2021.2.25700
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus as a comorbidity in COVID-19 infection in the United Arab Emirates

Abstract: Objectives: To compare risk factors and clinical outcomes among COVID-19 patients with or without diabetes in the United Arab Emirates (UAE). Methods: Data of 350 COVID-19 positive patients, admitted to Al Kuwait Hospital in Dubai, UAE, from February to May 2020 was collected retrospectively, including demographic data, clinical symptoms, blood tests, as well as radiographical assessments, and clinical outcomes of COVID-19. The design of the study is a retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 48 publications
(58 reference statements)
6
26
1
8
Order By: Relevance
“…In the present study we found that diabetes and hypertension are related to longer recovery period and CKD have no association with the recovery duration in COVID- This can be further observed in many studies where the number of COVID-19 infected males are as much as twice the number of COVID-19 infected female [18,33,39,40]. In our study we found that even though the number of COVID-19 admitted male patients are more than the twice of females.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study we found that diabetes and hypertension are related to longer recovery period and CKD have no association with the recovery duration in COVID- This can be further observed in many studies where the number of COVID-19 infected males are as much as twice the number of COVID-19 infected female [18,33,39,40]. In our study we found that even though the number of COVID-19 admitted male patients are more than the twice of females.…”
Section: Discussionsupporting
confidence: 75%
“…The rate of ICU admission among the COVID-19 infected patients is reported to be lower in other countries such as Republic of Korea [26], Mexico [27], America [28,29], United Arab Emirates [30] and Iran [31] than the present study. Similarly, the mortality rate reported in our study was lower than that reported in other studies from different countries like the United States of America [29,32], the United Arab Emirates [33].…”
Section: Discussioncontrasting
confidence: 48%
“…Researchers around the globe are still investigating the different factors and comorbidities that are associated with COVID-19 infection. Since this pandemic’s announcement, diabetes mellitus was considered one of the most common comorbidities with COVID-19 infection, where diabetic patients presented severe complications and higher mortality [ 2 , 3 , 4 , 5 , 6 , 28 ]. Upon shedding of ACE2 by ADAM17 from the cell surface, it can be found in a soluble form circulating in the serum/plasma of individuals [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan hasil pencarian dan seleksi artikel, ditemukan 6 (enam) studi yang sesuai dengan tujuan penelitian mengenai faktor risiko terjadinya Covid-19 pada penderita DM tipe 2 menggunakan pendekatan literature review. Dua studi dalam penelitian ini menggunakan desain studi retrospektif (Guo et al, 2020;Smith et al, 2021), dua studi menggunakan studi kohort retrospektif (Shang et al, 2021;Elemam et al, 2021)…”
Section: Hasil Dan Pembahasanunclassified
“…Hasil penelitian (Elemam et al, 2021), melaporkan bahwa diabetes melitus merupakan komorbiditas Covid-19 karena pasien diabetes menunjukkan gejala Covid-19 yang lebih parah serta menyebabkan hasil klinis kritis seperti masuk ICU dan kematian. Kejadian Covid-19 pada penderita DM, sebagian besar dialami oleh laki-laki dengan rata-rata usia 53.73 tahun.…”
Section: Pembahasanunclassified